(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
The present study was aimed to find out the frequency of obesity phenotypes and to correlate adipocyte dysfunction with different obesity phenotypes. A total of 1,507 apparently healthy adults attending the outpatient department were grouped into three based on body mass index which were then further categorized into six groups according to metabolically unhealthy or healthy phenotypes by the presence or absence of metabolic syndrome. Of them, metabolically obese normal weight, overweight, healthy obese and unhealthy obese groups were included as obesity phenotypes. Then by purposive sampling, leptin and adiponectin concentration of 184 subjects with different phenotypes were measured to find out the adipocyte dysfunction. Metabolically obese overweight followed by metabolically unhealthy obese were more prevalent i,e., 24.9% and 19.5%. All obesity phenotypes except metabolically obese normal weight were significantly documented with adipocyte dysfunction (p<0.05).